Modelagem territorial de cenário da expansão das plantações de eucalipto no Brasil - Alessandro Ribeiro Campos (2013)
Brazil experienced several cycles of expansion of forestry projects, resulting today in an area of 6.6 million hectares of planted forests. The growing demand and attractive prices of some wood products, added to the competitive advantages of forestry suggest continued expansion of plantations in the country. This trend requires that the earth system is managed and used as efficient as possible and relates to the necessity of knowledge concerning the use change associated with the expansion of planted forest. In this study, a spatially explicit model was developed to project and simulate the expansion of forest plantations in Brazil in the period 2012-2022, assuming a scenario without further deforestation and no competition with the production of major brazilian agricultural commodities, occupying only pastures. The future level of production forestry in the country was estimated from published plans by the brazilian government and the trends in production of major wood products of planted forests. The spatial model integrates components of macro-and micro-scale, profitability and favorable climate, to simulate the spatial dynamics of forest plantations. The results indicate that the total demand for wood from forests planted in 2022 will reach between 191 million m3 and 220 million m3. To meet this demand for industrial wood an average annual rate of planting 400-460 hectares in new areas will be necessary. The total area covered by planted forests is estimated at 9.9 million hectares in 2022, representing an increase of 51% within ten years. If you consider this planting in disturbed areas, only this expansion implies a 1.5% reduction of grazing areas. This study demonstrates the potential feasibility of expanding the planted forests in Brazil, in addition to the projected agricultural expansion and deforestation without directly associated, raising the possibility of occupation of those areas with potential for productive recovery. Contributes to strategies for territorial management and thus for efficient use of available land. To do so, need public policies that enforce the direction of expansion of the sector, minimizing potential conflicts and, above all, the marginal effects of the allocation of land use, which could neutralize specific environmental benefits.